Is it safe to eat? enjoy eating and minimize food risks - Shaw, Ian. (Springer Berlin Heidelberg, 2005)
Does your perception of food risks closely mirror the real risks? The reality is not what you think it is! Nobody would expect to die of cyanide poisoning after eating an almond cake - but if you tell them there is cyanide in it, they might think at least twice about eating it. Do you know that you are spreading an aerosol of Camphylobacter bacteria around your kitchen and on other food that may lay around - and thus creating possibly life-threatening toxins - just by washing an oven-ready chicken from the supermarket before roasting it? The author, Ian Shaw, PhD, discusses all these and many other important problems and questions - ranging from GM food to natural toxins - in his easily understandable, passionate, yet authoritative and informative book. But in contrast to many other authors, Ian Shaw sets the risks of food, foodborne pathogens and food contaminats in the context of life’s risks. Enjoyment of food and eating is a benefit that far outweighs the risks, at least if everybody is aware of those risks and uses measures to minimize them. Food safety through the ages -- Food is just one of life’s risks -- Bacteria in food — Good or bad? -- Viruses -- Mad cow disease and the elusive prion -- Natural toxins in food -- Agrochemical residues in food -- Gender bending chemicals in food -- Genetically modified food -- Is it safe to eat?.